COMA HYPOGLYCÉMIQUE PROFOND RÉVÉLANT UN SYNDROME DE SHEEHAN : A PROPOS D’UN CAS OBSERVÉ EN RÉANIMATION POLYVALENTE DES CLINIQUES UNIVERSITAIRES DE LUBUMBASHI EN RD CONGO - Eddya, Wasso Milinganyo; Sandraa, Sagboze Zalambo; Foremana, Mabala Kipulu; Ildephonsea, Teta wa Mwanza; Yves, Mukalay Banza; Dimitri, Kanyanda Nafatalewa; Roger, Munan Mwazaz; Yves, Isango Idi; Christian, Kakisingi Ngama; Christian, Tshisuz Nawej; Kaya, Kahambwe Mukonkole; Michel, Manika Muteya; et al. (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2022)
The intensive care unit remains a paradigm of rare pathologies culminating in often unusual syndromes.Sheehan's syndrome (SS) is a potentially serious postpartum complication which corresponds to ischemic necrosis of the anterior pituitary related to postpartum hemorrhage. It remains topical despite the improvement in gynecological and obstetrics management. The diagnosis, which is usually made only several years after the obstetrical event, by the presence of signs of anterior pituitary insufficiency, can however be early in the immediate postpartum and borrow serious acute forms which are real metabolic and endocrine emergencies. (1).Sheehan's syndrome is usually diagnosed several years after childbirth; therefore, it was recognized as a chronic disease. However, in some cases, Sheehan syndrome presents with acute symptoms and this variant can be life-threatening (2). We report a particular and complex revelation of Sheehan syndrome in a 36-year-old woman, who arrived in emergency in a coma with breathing difficulties and oxygen saturation at 60%. His coma is deep and the biological cause is urgently revealed to be hypoglycemia. She was taken care urgently and her extensive work-up revealed an anterior pituitary insufficiency with mainly corticotroph, lactotrope and somatotrope damage. Her obstetrical history is obvious revealing abundant peripartum hemorrhage following a retroplacental hematoma resulting in a maternal salvage caesarean section 10 years ago. His CT scan is normal.